Physical and Chemical Characteristics of Meloxicam from Nanostructured Lipid Carriers System Using Some Concentration Ratios of Monostreanin and Alpha-Tocopherolacetate Lipid Matrix - Yulia Anggraeni (Innovare Academic Sciences, 2017)
Objective: The objective of this research is to develop nanostructured lipid carriers (NLC) of meloxicam (MLX) for topical application using monostearin and alpha-tocopherol as lipid matrix.Methods: MLX-NLC was prepared by high-shear homogenization, and it was characterized for organoleptic, pH, viscosity, particle size and size distribution, zeta potential, crystallinity, morphology, and entrapment efficiency. The six different ratios of solid and liquid lipid matrix were 70:30, 75:25, 80:20, 85:15, 90:10, and 95:5, respectively.